Forecasting the critical role of intermittent therapies for the control of bone resorption. (August 2019) - Idrees, M; Sohail, Ayesha; Javed, Sana
Abstract: Background: Osteoporosis is a chronic metabolic disease characterized by an imbalance of bone resorption and formation, leading to bone fragility and increased susceptibility to fracture. Parathyroid hormone is approved therapy for the treatment of osteoporosis. Methods: The intermittent therapy of parathyroid hormone requires accurate administration. Meta-analysis is conducted to draw a clear picture of the impact of intermittent therapy and dose rates relative to time, on the osteoporotic patients. A novel mathematical model is presented in this article synchronised with the parametric values, depicted from meta-analysis. Findings: Results obtained from the mathematical model are in close agreement with the results obtained from the clinical trials. The model can be used to forecast the drug potency and dosage rates, to control the vicious cycle of osteoporosis. Interpretations: The intermittent administration of parathyroid hormone, rather than the continuous administration, is more effective, furthermore it is also concluded that a mathematical model, linked with the extensive literature of clinical trials, using meta-analysis can help in drug administration and future clinical studies of drug development. Highlights: Parathyroid hormone is approved therapy for the treatment of osteoporosis. The intermittent therapy ofParathyroid hormone requires accurate administration. Clinical trials and their conclusions are revisited for analysis. A novel mathematical model is synchronised with meta-analysis. Dose rates for intermittent therapy, relative to time are presented.